Social Justice and the Word: Keeping Diversity Alive in Therapeutic Conversations - Paré, David (Canadian Journal of Counselling and Psychotherapy, 2014)
The question of social justice is gaining attention in examinations of the scope of counselling and psychotherapy practice. There is a growing recognition that persons seeking therapeutic services are not merely manifesting individual personalities, but dealing with social inequities that help to illuminate the problems they describe. An outgrowth of this insight is the call to expand the therapist’s role into advocacy by extending the practice of counselling beyond the consulting room. Although celebrating these developments, this article makes a case for how social justice and injustice not only unfold in the broader social arena; they also play out, utterance by utterance, in therapeutic conversations. After demonstrating how therapeutic conversations can be understood as sites of identity construction, the article offers a range of questions for aiding practitioners in “doing justice” in their exchanges with clients.